THE CONSEPT OF ANTONYMY AND ITS LINGUISTIC FEATURES - Usmanova Kamola Xikmatullayevna,Tojiddinov Otabek Sayfiddinxo’ja o’g’li (International Journal of Literature and Language Studies, 2026)
This thesis examines the concept of antonymy and its linguistic features in modern linguistics. Antonymy is one of the fundamental semantic relations that expresses opposition between lexical units. The study analyzes the main types of antonyms, their semantic characteristics, stylistic functions, and their role in communication. The research also highlights the importance of antonymy in English and Uzbek linguistics, emphasizing how oppositional meanings contribute to expressive and effective speech.